Study of frequency and inheritance model of ACE1 I/D and ACE2 rs2285666 polymorphisms in COVID‐19 patients with varying severity of lung involvement and its effect on serum cytokines levels. (13th December 2022) - Beyranvand, Shirin; Davoodian, Parivash; Alizade, Hesam; Gouklani, Hamed; Nejatizadeh, Azim; Eftekhar, Ebrahim; Nikpoor, Amin Reza
Abstract: The angiotensin‐converting enzyme (ACE) has been shown to play a role as a receptor for the COVID‐19 virus. This virus usually gets into cells and infects them by attaching to their glycoprotein receptors, which are found on the ACE2 receptor. The aim of this study was to evaluate the frequency and inheritance of ACE1 I/D and ACE2 rs2285666 polymorphisms in COVID‐19 patients with varying severity of lung involvement and its effect on serum cytokines levels of interleukin (IL)‐1 and IL‐6 and laboratory parameters. One hundred eighty‐five COVID‐19 patients were grouped according to the severity of lung involvement. (I/D) polymorphism of the ACE1 gene and rs2285666 polymorphism of the ACE2 gene were determined by single specific primer‐polymerase chain reaction and restriction fragment length reaction‐polymerase chain reaction methods, respectively. Serum levels of IL‐1 and IL‐6 were also measured by the enzyme linked immunosorbent assay technique. No statistically significant association of ACE2 rs2285666 polymorphism genotypes and ACE1 I/D with the severity of lung involvement was noted. However, there was a statistically significant association between I/D ACE1 polymorphism genotypes and IL‐6, white blood cells (WBC), and neutrophil‐to‐lymphocyte ratio (NLR) levels. Also, there was no statistically significant association between rs2285666 polymorphism genotypes and patients' blood oxygen saturation level, IL‐6, IL‐1β, lactate dehydrogenase activity, WBC count, and NLR. In patients with COVID‐19, the rs2285666 polymorphism of the ACE2 gene and the I/D polymorphism of the ACE1 gene were not significantly associated with the severity of COVID‐19 disease and serum IL‐6 and IL‐1 cytokine levels.